Urgensi Strategi Perencanaan Bisnis, Dukungan Pemerintah, dan Manajemen Inovasi dalam Keberlanjutan Bisnis - Rohmatiah, Ahadiati; Nugroho, Sigit Sapto; Mutmainah, Mutmainah; Aribowo, Wira Ganet (Jurnal Samudra Ekonomi dan Bisnis, 2026)
MSMEs in Madiun City and Regency receive excellent attention and support, but still experience the phenomenon of "opening" and "closing." This study aims to analyze the influence of planning strategies, government support, innovation management, and business sustainability regarding this phenomenon. This quantitative research was conducted by distributing questionnaires to 347 MSMEs located in Madiun City and Regency. The analysis technique used multiple linear regression with the SmartPLS 4 program. The results showed that partially, planning strategies had no effect on MSME sustainability, but government support and innovation management were proven to influence this condition. Simultaneously, all three were proven to influence MSME sustainability. Based on these findings, MSMEs are recommended to carry out sustainable innovations that can attract the public, whether in the form of product innovation, service innovation, management innovation, or marketing innovation.